Total Intracranial Migration of VP shunt - A Case Report (Bangladesh Journal of Neurosurgery, 2020)
Ventriculoperitoneal (VP) shunt is a common procedure performed for treatinghydrocephalus. Recently, endoscopy has been used in selected cases. Proximalmigration of VP shunt is a rare complication. Complete intracranial migration of VPshunt is very rare with very few cases reported in literature. We report a case ofcomplete intracranial migration of a VP shunt which was endoscopically retrieved.The possible mechanisms causing this very uncommon complication and themanagement are explained.Bang. J Neurosurgery 2020; 9(2): 168-172